Development of an IoT-Based Automatic Remote Health Monitoring System (Journal of Engineering Science, 2024)
A well-planned health monitoring system is essential for the modern health center, and a portable remote health monitoring system with many intellectual features is becoming a great improvement in healthcare arrangements. The proposed system includes various micro-electronics medical devices and applications that come through network-connected devices and help to monitor patients' real-time medical data. In this paper, the patient's health condition has been monitored by using the four types of major health parameters temperature sensor, heart pulse rate sensor, blood pressure sensor module, and blood oxygen (SpO2) sensor. All the sensor nodes are connected to the Raspberry Pi-based embedded system. The real-time health data are recorded, stored, and transmitted to the doctor via the internet with the help of a Raspberry Pi-based embedded system and IoT server. The system will benefit the patient from remote areas with quick diagnosis, remote observation, home observation, and a medical data storage system.Journal of Engineering Science 14(2), 2023, 21-30